Welcoming the Other (Outsider): The Psychotheological Approach of Ruth 4:13-17 - Salomo Sihombing; Erman Sepniagus Saragih (Pharos Journal of Theology)
Psychotheology is described as a careful study of how one's mental processes, emotive experiences, and behavioural patterns interact with Biblical truths. The psychotheological approach of Ruth 4:13-17, by focusing on Ruth’s status as a foreigner (the other-outsider), explores about the significance of transformation or movement. The transformation of Ruth as a foreign woman (the other) makes her become a significant figure in Israel (Betlehem). Based on a psychotheological analysis of Ruth’s alienation as a Moabite woman, this article seeks to analyze Israelite inconsistency in order to show hospitality towards “the other” in society. God has commanded the Israelites to embrace “the other” (foreigners). The methodology applied in this study was a qualitative one based on literature review. Therefore, the first stage was to analyze the psychological impact perspective on foreign women in Old Testament (OT) times generally through the story of Ruth (Ruth 4:13-17). The second stage was the hermeneutical process of Ruth 4:13-17 theologically. Through the integration between psychology and theology (psychotheological approach) this study uncovered that openness is the key to embrace “the other” (outsider) and/or “marginalized people”. God Himself always opens and welcomes people who seek refuge in Him. The story of Ruth teaches us all about love, loyalty, and the transformative power of faith in God. It also highpoints Ruth's steadfast commitment to Naomi, and her devotion to God. It also demonstrates for us the surprising ways God can work in unforeseen situations, even for those who are often perceived to be outsiders.